Characterization of indoor/outdoor settled dust and air pollutants in Damaturu, Nigeria - Mohammed, Fatima S.; Crump, Derrick (IJET, 2013)
This paper presents results of on-going experiments being undertaken to characterise the composition of settled dusts and some airborne contaminants in homes and outdoors in Damaturu, north-eastern Nigeria. These have involved the physical analysis of the dust samples collected from different homes by scanning electron microscopy (SEM) which showed images of particles of 2µm to 50µm and fragmented filamentous particles of 50µm to 200µm. Microbiological analysis conducted include media culture and microscopic observations where a range of fungal and bacterial colonies were identified with colony forming units in settled dust and air of between 1.02  10 4 to1.18  10 5 CFU g -1 and 1.07  10 4 1.69  10 5 CFU m -3 (for fungi)and 7.70  10 3 to1.14  10 5 CFU g -1 , 1.90  10 3 to 1.13  10 5 CFU m -3 (for bacteria) . Metal analysis by ICP-MS (total quant method) of the settled dusts revealed the presence of metal elements in the range of Al>Na>Mg>Ca>K>P>Si>Mn>Ti and indicated the maximum concentration of Lead, Copper, Cadmium, Nickel and Zinc (mg kg -1 ) to bePb-89.7, Cu-68.4, Cd-15.6, Ni-14.9, Zn-1.15.The results also revealed the presence of organic chemical pollutants in varying concentrations in the indoor and outdoor dusts and airborne samples within different homes; eight semi-volatile and volatile organic compounds(SVOCs/VOCs); benzene, hex anal, nonanal, diethyl phthalate (DEP), diisobutylphthalate (DIBP), dibutylphthalate (DBP), and diethylhexylphthalate (DEHP) and limonene were quantified among the numerous organic chemicals present in the samples analysed based on their frequency of occurrence in the samples collected, as well as their potential health effects arising from short term and long term exposure as reported in earlier studies. The results suggested that the indoor environments contain considerably more organic chemical pollutants than the outdoors. From the results obtained so far on the chemical, metal, and biological pollutants present as well as the physical characteristics of indoor dusts from Nigerian homes, it can be ascertained that the dusts act as a reservoir of pollutants that can increase peoples’ exposure and be a risk to the health of residents of the community.
Keywords: House dust; indoor air; harmattan haze; dust storm; pollutants